Estimating the quality of YouTube videos on pulmonary lobectomy - Chen, Zixuan (J Thorac Dis, 2019)
BACKGROUND: YouTube is a valuable source of medical videos, but the quality of the videos is difficult to determine. This study aimed to estimate the quality by characteristics of the surgeon and by view rate. METHODS: The term, “pulmonary lobectomy”, as a keyword was searched for on the YouTube search engine with the filter set to sort videos by view rate. The data of the first 100 videos were gathered and analyzed. A search was performed for any surgeon who was featured in a video or who posted a live video on Scopus to ascertain the h-index and lung-related publication history. RESULTS: There were approximately 8,650 videos that were found using “pulmonary lobectomy” as the search term. In the top 100 videos, there were 79 live surgical videos, 12 academic informational videos, 5 patient interviews, and 4 other miscellaneous videos. A primary surgeon was identified in 54 of the 79 (68%) live surgeries, with the majority of these surgeons having an adequate academic affiliation such as an h-index and academic publications. CONCLUSIONS: There are a large amount of YouTube videos on pulmonary lobectomy with acceptable quality, and these videos may have great potential to improve surgical education. But trainees should critically examine the quality of video content. Furthermore, these surgical videos should be improved in quality before they can be used in medical teaching.